Stripping and Excavating Control Technology of Spontaneous Combustion Area in Shallow Buried Coal Seam - Xin-hai Zhang (E3S Web of Conferences, 2021)
The article expounds the principle, steps and results of detecting the fire source by the magnetic method. Based on the determination of the fire source range, by analyzing the actual situation of the shallow coal seam, comparing the advantages and disadvantages of the three different treatment methods and the applicable situation, a stripping is proposed. The law governs the fire zone and applies it in the governance zone. The results show that the magnetic detection technology has high detection accuracy and fast efficiency, and the stripping method has good fire extinguishing effect in the fire area, high safety, large amount of residual coal recovery, and is suitable for shallow buried fire sources. The study provides a scientific basis for fire detection, treatment, coal resource recovery, environmental protection and economic development in open-pit mine fire areas.